Evaluación In Silico De La Afinidad De 12 Moléculas Sobre Proteínas Involucradas En La Formación De Biopelicula De Streptococcus Mutans (2022)
Of the infectious diseases affecting humans, dental caries is probably the most prevalent. Dental caries is described as a dynamic process of demineralization and remineralization, a product of bacterial metabolism on the tooth surface, which over time can produce a net loss of minerals and possibly, but not always, result in the presence of a cavity. Oral bacteria belong to a complex community of numerous species that participate in the formation of bacterial plaque (biofilm or biofilm) with all its functions, interactions and properties. The current concept contemplates that several microorganisms are included in the pathogenesis of dental caries, with Streptococcus mutans being the most important agent associated with it. Streptococcus mutans has different proteins involved in biofilm formation. Bioinformatics strategies for the search of drugs for the treatment of different diseases can be used in dentistry, so with this work it was possible to evaluate In silico the affinity of twelve molecules on proteins involved in the biofilm formation of Streptococcus mutans. Twelve molecules previously reported by (Rivera-Quiroga et al., 2021) were selected and remote docking with six proteins GBP-C, CE4 esterase, GTF-C, sortase A and two Ag I/II domains were performed to identify the affinity of these molecules on these proteins